Selection of physiological spermatozoa during intracytoplasmic sperm injection. (1st April 2016) - Torki‐Boldaji, B.; Tavalaee, M.; Bahadorani, M.; Nasr‐Esfahani, M. H.
Summary: Sperm genomic integrity has a significant effect on intracytoplasmic sperm injection (ICSI) outcomes, especially post‐implantation. Spermatozoa selected based on motility and morphology do not guarantee the genomic integrity of spermatozoa. Nearly fifty percentage of spermatozoa in infertile men with normal morphology present different degrees of DNA fragmentation. However, capacitated or hyperactivated spermatozoa show lower degrees of DNA fragmentation. Therefore, selection of hyperactivated spermatozoa may improve ICSI outcome. Routinely, for ICSI, fast‐moving spermatozoa with A or B motility pattern are mainly selected for injection. The result of this study shows that in processed semen samples, hyperactivated spermatozoa are mainly observed in B motility pattern while, in viscous medium like polyvinylpyrrolidone (PVP), hyperactivated spermatozoa are mainly present in spermatozoa with C pattern of motility (nonprogressive). Therefore, we propose spermatozoa with C motility pattern which contains the main population of physiological or hyperactivated spermatozoa should be selected for ICSI.